Getting in touch: Communication in physical therapy practice and the multiple functions of language - Ahlsen, Birgitte; Nilsen, Anne Birgitta (Frontiers in Rehabilitation Sciences, 2022)
In physical therapy, communication that actively involves the patient is seen as the foundation of patient-centered treatment. Research on communication in physical therapy highlights how patients’ opportunity to actively participate is often limited by the therapists’ focus on biomedical facts and clinical tasks. However, little is known about aspects of communication in clinical practice that may promote patients’ active participation. The aim of this study was to gain knowledge about verbal and nonverbal communication used by physical therapists in interactions with patients and how this may contribute to encouraging patients’ participation. The selected case is from a qualitative observational case study of the first encounter between a female physical therapist and a male patient with chronic neck pain. Drawing on theories about communication and the metafunctions of language, the findings highlight how the therapist’s use of verbal resources, such as leaving sentences unfinished and repeating the patient’s words, helped promote the patient’s participation. The findings also show how the therapist’s use of nonverbal communication, such as touch, gaze, and accepting interruptions from the patient—contributed to the patient’s active participation. Demonstrations of the use of linguistic communication theory in this study may contribute to enhancing physical therapists’ self-awareness around communication, which is a fundamental element in patient-centered treatment.